UJI AKTIVITAS ANTIOKSIDAN TERHADAP DAUN BAKUNG (CRINUM ASIATICUM L.) DENGAN PELARUT ETANOL DENGAN METODE DPPH (2,2-DHIPHENYL-1-PIRCYLHYDRAZYL) - Natasya Louisa; Astriani Natalia Br Ginting; Nerly July Pranita Simanjuntak; Marlina L Simbolon (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2026)
Free radicals are one of the main factors causing oxidative stress, which contributes to various degenerative diseases. Natural antioxidants derived from plants have the potential to serve as safer alternatives to synthetic antioxidants. One plant with potential as a natural antioxidant source is bakung (Crinum asiaticum L.), which has long been traditionally used, although scientific studies on it remain limited. This study aimed to determine the antioxidant activity of the ethanol extract of bakung leaves (Crinum asiaticum L.) using the DPPH method and to examine its secondary metabolite profile. This experimental research employed maceration extraction using 96% ethanol, followed by phytochemical screening to identify classes of compounds and antioxidant activity testing using the DPPH method expressed as IC₅₀ values. The results showed that the ethanol extract of bakung leaves contains alkaloids, flavonoids, tannins, saponins, and triterpenoids/steroids. The antioxidant activity test indicated that the extract exhibited strong antioxidant activity with an IC₅₀ value of 13.73 µg/mL, although it was still lower than vitamin C as the positive control, which had an IC₅₀ value of 8.56 µg/mL. Based on these findings, it can be concluded that the ethanol extract of bakung leaves (Crinum asiaticum L.) has potential as a natural antioxidant source and holds promise for further development in the fields of pharmacy and natural product chemistry.